Profiling Near-surface Winds on Mars Using Attitude Data from Mars 2020 Ingenuity - Brian Jackson; Lori Fenton; Travis Brown; Asier Munguira; German Martinez; Claire Newman; Daniel Viúdez-Moreiras; Matthew Golombek; Ralph Lorenz; Mark D. Paton; Dylan Conway (The Planetary Science Journal)
We used attitude data from the Mars Ingenuity helicopter with a simple steady-state model to estimate wind speeds and directions at altitudes between 3 and 24 m, the first time winds at such altitudes have been probed on Mars. We compared our estimates to wind data from the meteorology package MEDA on board the Mars 2020 Perseverance rover and to predictions from meteorological models. Wind directions inferred from Ingenuity data agreed with the directions measured by MEDA, when the latter were available, but deviated from model-predicted directions by as much as 180° in some cases. The inferred wind speeds are often much higher than expected. For example, meteorological predictions suggest that Ingenuity should not have seen wind speeds above about 15 m s ^−1 during its 59th flight, but we inferred speeds reaching nearly 25 m s ^−1 . For flights during which we have MEDA data to compare to, inferred wind speeds imply friction velocities >1 m s ^−1 and roughness lengths >10 cm, which seem implausibly large. These results suggest that Ingenuity was probing winds sensitive to aerodynamic conditions hundreds of meters upwind instead of the conditions very near Mars 2020, but they may also reflect a need for updated boundary layer wind models. An improved model for Ingenuity’s aerodynamic response that includes the effects of transient winds may also modify our results. In any case, the work here provides a foundation for exploration of planetary boundary layers using drones and suggests important future avenues for research and development.